Legal Construction of Economic Violence in the Household as a Ground for Divorce in Religious Courts - Siti Aminah; Mohammad Sirojuddin (STAI Miftahul Ula Nganjuk, 2026)
Economic violence within the household constitutes one of the most pervasive yet least visible forms of domestic abuse in Indonesia. Despite its profound impact on the dignity, autonomy, and well-being of victims, the legal construction of economic violence as an autonomous ground for divorce in Religious Courts (Pengadilan Agama) remains contested and underdeveloped. This paper employs a normative legal research methodology, supplemented by analysis of judicial regulations and scholarly commentary, to examine how Indonesian positive law constructs economic violence as a basis for marital dissolution. The analysis traverses the key legislative instruments, including Law No. 1 of 1974 on Marriage, Government Regulation No. 9 of 1975, the Compilation of Islamic Law (KHI), and Law No. 23 of 2004 on the Elimination of Domestic Violence (UU PKDRT), together with the transformative impact of Supreme Court Circular Letter (SEMA) No. 3 of 2023, which established domestic violence as an independent divorce ground without the prerequisite of six months of separate dwelling. The findings reveal that while the normative framework progressively accommodates economic violence through the interpretive expansion of “severe abuse” (penganiayaan berat), significant gaps persist between de jure recognition and de facto judicial enforcement. Evidentiary challenges, cultural resistance, and the absence of explicit legislative integration of economic violence into divorce provisions continue to undermine effective legal protection. The paper concludes with recommendations for legislative reform, judicial training, and specialized evidentiary guidelines to strengthen the legal response to economic violence in Indonesian Religious Courts.